A modified energy equation model for flow boiling in porous media and its application to transpiration cooling at low pressures with transient effect. (September 2020) - Hu, Haowei; Jiang, Peixue; Ouyang, Xiaolong; Zhao, Cheng; Xu, Ruina
Highlights: The energy model is modified to study low-pressure effects on phase change process. Case studies are conducted on phase-changed transpiration cooling. Non-isothermal two-phase zone are observed at low pressures. Revealing vapor blockage mechanism to avoid thermal protection failure. Designing porous plate structure and dividing reservoir to remove vapor blockage. Abstract: With the rapid development of thermal management technology, flow boiling in porous media has been widely used in many applications. Among them, phase-changed transpiration cooling is a potential trend in the field of aerospace thermal protection. However, the dynamic response delay, change in boiling point at low pressure, and vapor blockage effect have resulted in significant challenges to its development, and it is difficult to achieve convergence with such non-linear transport equations. Here, kinetic enthalpy is used to restructure energy equation of multiphase mixture model to improved model convergence and accuracy. This modified equation is capable to consider temperature gradient in the two-phase zone, to eliminate non-physical jump and hold smooth transition between the single-phase and two-phase zone, and to enhance the model efficiency of the algorithm. The model was validated by the experiments and was applied to simulate real phase-changed transpiration cooling conditions without main flow effect. It was shown that at low pressure, the two-phase zone has reversed temperature gradient against single-phase zone, and the non-uniform heat flux applied to the boundary can cause non-uniform distribution of mass flux, which may block the vapor and lead to the failure of thermal protection. Subsequently, three ways are proposed to effectively remove vapor blockage and enhance flow uniformity, which are designing porous plate structure, coordinating mass flux distribution, and dividing reservoir into different chambers according to input heat flux. The better understanding of the response mechanism during dynamic process provides a fundamental knowledge to control methods during phase-changed transpiration cooling.